Effect of fingolimod on MRI outcomes in patients with paediatric-onset multiple sclerosis: results from the phase 3 PARADIGMS study. Issue 5 (4th March 2020) - Arnold, Douglas L; Banwell, Brenda; Bar-Or, Amit; Ghezzi, Angelo; Greenberg, Benjamin M; Waubant, Emmanuelle; Giovannoni, Gavin; Wolinsky, Jerry S; Gärtner, Jutta; Rostásy, Kevin; Krupp, Lauren; Tardieu, Marc; et al.
Abstract : Objective: PARADIG MS demonstrated superior efficacy and comparable safety of fingolimod versus interferon β-1a (IFN β-1a) in paediatric-onset multiple sclerosis (PoMS). This study aimed to report all predefined MRI outcomes from this study. Methods: Patients with multiple sclerosis (MS) (aged 10–<18 years) were randomised to once-daily oral fingolimod (n=107) or once-weekly intramuscular IFN β-1a (n=108) in this flexible duration study. MRI was performed at baseline and every 6 months for up to 2 years or end of the study (EOS) in case of early treatment discontinuation/completion. Key MRI endpoints included the annualised rate of formation of new/newly enlarging T2 lesions, gadolinium-enhancing (Gd+) T1 lesions, new T1 hypointense lesions and combined unique active (CUA) lesions (6 months onward), changes in T2 and Gd+ T1 lesion volumes and annualised rate of brain atrophy (ARBA). Results: Of the randomised patients, 107 each were treated with fingolimod and IFN β-1a for up to 2 years. Fingolimod reduced the annualised rate of formation of new/newly enlarging T2 lesions (52.6%, p<0.001), number of Gd+ T1 lesions per scan (66.0%, p<0.001), annualised rate of new T1 hypointense lesions (62.8%, p<0.001) and CUA lesions per scan (60.7%, p<0.001) versus IFN β-1a at EOS. The percent increases from baseline in T2 (18.4% vs 32.4%, p<0.001) and Gd+ T1 (–72.3% vs 4.9%, p=0.001) lesion volumes and ARBA (–0.48% vs −0.80%, p=0.014) were lower with fingolimod versus IFN β-1a, the latter partially due to accelerated atrophy in the IFN β-1a group. Conclusion: Fingolimod significantly reduced MRI activity and ARBA for up to 2 years versus IFN β-1a in PoMS.